2020
DOI: 10.1136/bmj.m3081
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the global response to climate change and infectious disease threats

Abstract: Strengthening the global response to climate change and infectious disease threats Climate change is emerging as an important driver of disease incidence, and a wait and see approach invites unnecessary risk, write Jeremy Hess and colleagues. Governments, funders, researchers, and practitioners must act now

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 66 publications
0
33
0
1
Order By: Relevance
“…Increasingly, a growing number of infectious health outcomes are associated with climate change that are inequitably distributed within and between European countries. Weather parameters contribute in a nonlinear way to infectious disease transmission 3 and have been shown to be one of the key drivers of the emergence, re-emergence, and spread of infectious disease 4 , 5 . Moreover, they contribute to the survival, reproduction and distribution of disease pathogens and vectors, as well as to their transmission and geographical patterns 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, a growing number of infectious health outcomes are associated with climate change that are inequitably distributed within and between European countries. Weather parameters contribute in a nonlinear way to infectious disease transmission 3 and have been shown to be one of the key drivers of the emergence, re-emergence, and spread of infectious disease 4 , 5 . Moreover, they contribute to the survival, reproduction and distribution of disease pathogens and vectors, as well as to their transmission and geographical patterns 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have projected that climate action would reduce noncommunicable [ 235 ] and communicable disease threats [ 236 ]. A recent study in Europe found that at least 51,000 premature deaths per year could be avoided by following guidelines on air pollution [ 237 ].…”
Section: Positive Externalities Of Mitigation and Adaptation: A Stmentioning
confidence: 99%
“…Studying microbial evolution associated with climate change is a way of understanding the adaptation mechanisms of microbes, when facing changes in abiotic factors, such as: elevated temperature, increased CO 2 , increased salinity and altered water availability [ 47 ]. It is worth noting that there are some on-going discussions focused on how climate change is likely leading to increased health issues, namely by changes in microbial biodiversity and distribution, in microbial composition and function, in microbial physiological responses with phenotypic shifts and evolutionary adaptations, as well as cases of increased pathogenicity and potentially depressed immunity [ 6 , 48 , 49 , 50 , 51 , 52 ]. It is now known that climate change aggravates the global spread of pathogens (vector borne, foodborne, airborne, waterborne and other environmental pathogens) and their associated diseases, stresses marine life causing disease and disrupting regular ecosystem functions, and increases antimicrobial resistance of microorganisms, threatening life on Earth, human health, and food security [ 53 ].…”
Section: Introductionmentioning
confidence: 99%